Use of Preventive Medication in Patients With Limited Life Expectancy: A Systematic Review - Poudel, Arjun; Yates, Patsy; Rowett, Debra; Nissen, Lisa M. (Journal of pain and symptom management, 2017)
Optimal prescribing in patients with limited life expectancy (LLE) remains unclear. This study systematically reviews the published literature regarding the use of preventive medication in patients with reduced life expectancy. A systematic literature search was conducted using three databases (MEDLINE, EMBASE, and CINAHL). Articles published in English from January 1995 to December 2015 were retrieved for analysis to identify peer-reviewed, observational studies assessing use of preventive medications in patients with LLE. Inclusion criteria were: patients with a LLE (less than or equal to two years); prescribed/used preventive medications. Of the 15 studies meeting our eligibility criteria, six were from inpatient hospital settings, five in palliative care, three in nursing homes, and one in community settings. The most common life-limiting illnesses described in the studies were cancer (n = 6), cardiovascular diseases (n = 4), dementia and cognitive impairment (n = 2), and other life-limiting illnesses (n = 3). Lipid-lowering medications, especially the statins were frequently prescribed preventive medication followed by antiplatelets, angiotensin converting enzyme inhibitors and angiotensin receptor blockers, anti-osteoporosis medications, and calcium channel blockers. Only four studies reported the instances of medication withdrawal. Patients continue to receive medications that are not prescribed as symptomatic treatment despite having a LLE. Very few rigorous studies have been conducted on minimizing preventive medications in patients with LLE, and expert opinion varies on medication optimization at the end of life. A consensus guideline that addresses this gap is of paramount importance.